STUDI ETNOMEDISIN DI INDONESIA DAN PENDEKATAN PENELITIANNYA - Silalahi, Marina (Jurnal Dinamika Pendidikan, 2016)
ABSTRACTIndonesia has about 25000-30000 species of plants and inhabited by 300-700 ethnic.The ethnic groups in Indonesia uses of plants for variety of purposes, one of them asmedicine. The uses of plants as medicine passed on orally and thus susceptibledegraded. Ethnomedicine studies is can be use to documentation of medicinal plantsby ethnics through scientifically research methods. This article aims to explain theethnomedicine studies in Indonesia and its approach research methods. This paper isbased on literature offline and online media. Ethnomedicine is perception andconception of ethnic/local communities to health concept by local ethnics.Ethnomedicine studies in Indonesia was initiated by Rumphius on century 19th whichdocumention of uses of plant by local etnich Ambon. Those are documented in thebooks with entitle Amboinense Herbarium. Heyne in 1927 recorded 1040 spesieswhich uses by local ethnic Indonesia, that are documented in the book entitled Denuttige planten van Nederlandsch. Research continues to increased, but mainconcentrated in Java and Bali, while the other islands is few. Ethnomedicine studiescan be approaches do public surveys and market surveys. Data obtained from thesurvey can be analyzed with use value (UV) Index of Cultural Significance ICS, andFidalety level (FL).Keywords: Ethnomedicine studies, use value (UV) Index of Cultural SignificanceICS, and Fidalety level (FL)ABSTRAKIndonesia memiliki sekitar 25.000-30.000 spesies tumbuhan dan dihuni sekitar 300-700 etnis. Etnis-etnis tersebut memafaatkan untuk berbagai tujuan, salah satunyauntuk tujuan pengobatan. Pemanfaatan tumbuhan sebagai bahan obat sebagian besardiwariskan secara lisan sehingga rentan terdegradasi. Studi etnomedisin merupakansalah satu cara yang dapat digunakan untuk medokumentasikan pemanfaatantumbuhan oleh etnis dengan metode penelitian yang dapat diterima secara ilmiah.Tulisan ini bertujuan menjelaskan studi etnomedisin khususnya di Indonesia danmetode penelitiannya. Tulisan ini didasarkan pada literatur offline and online media.Etnomedisin adalah presepsi dan konsepsi etnis/masyarakat lokal dalam memahamikesehatan. Studi etnomedisin di Indonesia diawali oleh Rumphius pada abat ke-19yang mendokumentasikan pemafaatan tumbuhan oleh masyarakat Ambon danpulau-pulau yang didokumentasikan dalam buku Herbarium Amboinense. Heynepada tahun 1927 mencatat sebanyak 1040 tumbuhan bermanfaat obat yangdidokumentasikan pada buku berjudul Tumbuhan Bermanfaat Indonesia. Penelitianterus berkembang, namun sebagian besar memusatkan di pulau Jawa dan Bali,sedangkan pulau lainnya masih sedikit. Penelitian etnomedisin dapat dilakukanpendekatan survei masyarakat dan survei pasar. Data yang diperoleh dari survei dapatdianalisis dengan use value (UV), Index of Cultural Significance ICS, dan Fidalety level(FL).Kata Kunci: Etnomedisin, use value (UV), Index of Cultural Significance ICS, danFidalety level (FL)